The myth of generational conflict : the family and state in ageing societies - Arber, Sara, 1949-; Attias-Donfut, Claudine (London ; New York : Routledge, 2000)
The ageing of Western societies has provoked extensive sociological debate, surrounding both the role of the state and whether it can afford the cost of an ageing population, and the role of the family, especially women, in supporting older people. In this important book, the authors examine how changes, such as cuts in welfare provision, migration, urbanization and individualisation influence intergenerational relations. The collection addresses theoretical and policy issues connecting age and generation with the family and social policy, and focuses both on cross-cultural compariso.
Chapter 1 EQUITY AND SOLIDARITY ACROSS THE GENERATIONS / Claudine Attias-Donfut -- chapter 2 THE REDISTRIBUTIVE EFFECTS OF GENERATIONAL TRANSFERS / Claudine Attias-Donfut -- chapter Transfers across three generations -- chapter 3 Complementarity between private and public transfers / Claudine Attias-Donfut -- chapter 4 Wealth distribution between generations -- A source of conflict or cohesion? / Lars Gulbrandsen -- chapter 5 Families apart? Intergenerational transfers in East and / Martin Kohli -- chapter Acknowledgements -- chapter 6 Generational relations and the law / Marjatta Marin -- chapter References -- chapter 7 Discontinuous change and generational contracts / Henk Becker -- chapter 8 Gender, the generational contract and pension privatisation / Jay Ginn -- chapter 9 Trail-blazers and path-followers -- Social reproduction and geographical mobility in youth / Gill Jones -- chapter The study -- chapter 10 The transmission of life stories from ethnic minority fathers to their children -- A personal resource to promote social integration / CATHERINE DELCROIX -- chapter 11 Reinventing the generational contract -- Anticipated care-giving responsibilities of younger Germans and Turkish migrants / Dagmar Lorenz-Meyer -- chapter Notes -- chapter 12 Continuity and change -- The family and community life of older people in the 1990s / Miriam Bernard -- chapter Social networks, social support and the baseline studies.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Intergenerational relations -- Europe; Conflict of generations -- Europe; Relations entre générations -- Europe; Conflit de générations -- Europe; FAMILY & RELATIONSHIPS -- Conflict Resolution; FAMILY & RELATIONSHIPS -- Abuse -- Elder Abuse; FAMILY & RELATIONSHIPS -- Family Relationships; Conflict of generations; Intergenerational relations; Europe